Carbon Sources Tune Antibiotic Susceptibility in Pseudomonas aeruginosa via Tricarboxylic Acid Cycle Control. Issue 2 (16th February 2017) - Meylan, Sylvain; Porter, Caroline B.M.; Yang, Jason H.; Belenky, Peter; Gutierrez, Arnaud; Lobritz, Michael A.; Park, Jihye; Kim, Sun H.; Moskowitz, Samuel M.; Collins, James J.
Summary: Metabolically dormant bacteria present a critical challenge to effective antimicrobial therapy because these bacteria are genetically susceptible to antibiotic treatment but phenotypically tolerant. Such tolerance has been attributed to impaired drug uptake, which can be reversed by metabolic stimulation. Here, we evaluate the effects of central carbon metabolite stimulations on aminoglycoside sensitivity in the pathogen Pseudomonas aeruginosa . We identify fumarate as a tobramycin potentiator that activates cellular respiration and generates a proton motive force by stimulating the tricarboxylic acid (TCA) cycle. In contrast, we find that glyoxylate induces phenotypic tolerance by inhibiting cellular respiration with acetyl-coenzyme A diversion through the glyoxylate shunt, despite drug import. Collectively, this work demonstrates that TCA cycle activity is important for both aminoglycoside uptake and downstream lethality and identifies a potential strategy for potentiating aminoglycoside treatment of P. aeruginosa infections. Graphical Abstract: Highlights: Central carbon perturbations alter aminoglycoside susceptibility in P. aeruginosa TCA cycle activation of respiration and PMF overcomes aminoglycoside tolerance Shunting of the TCA cycle biochemically protects against aminoglycoside lethality Aminoglycoside lethality requires both drug uptake and downstream TCA cycle activity Abstract : Meylan et al. investigate mechanisms underlying antibiotic susceptibility in the cystic fibrosis pathogen Pseudomonas aeruginosa . Taking a systems approach, they find TCA cycle and respiratory activity to be important for both the uptake and the downstream lethality of aminoglycoside antibiotics.